Nanoforming behaviour and microstructural evolution during nanoimprinting of ultrafine-grained and nanocrystalline metals - Ast, Johannes; Durst, Karsten (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
The influences of microstructure and the macroscopic material behaviour on the nanoforming behaviour of nickel, copper and aluminium with grain sizes ranging from single crystalline to nanocrystalline were studied using a flat punch indenter with a double ring cavity and with a wheel-shaped die. Of main interest in this work was the flow of crystalline materials in submicron sized cavities during imprinting. The ring cavities which have widths of 650 nm and 80 nm were fabricated by focused ion beam (FIB) machining. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to evaluate the imprinted ring geometries. The microstructure after imprinting was investigated in detail by FIB cross sections and electron back scatter diffraction (EBSD) as well as by using finite element analysis (FEA) of the forming process. SX-Ni showed the smallest extrusion height together with a sinking-in of the formed region. This is accompanied by strong orientation gradients up to 18° below the cavities. The UFG samples exhibited the best formability, with a subgrain formation inside and around the cavities. The plastic flow is confined to the surface and a pile-up formation occurs. For the nanocrystalline material only a slight elongation of the grains inside the cavity was found, yielding moreover a smooth and homogeneous extruded geometry. These findings can be explained by the grain size to cavity width ratio as well as the yield strength and the work hardening behaviour of the materials.
WW1::976